Metropolis and the media in the contemporary TV representations - Rafele, Antonio; Tarquini, Federido; Vagni, Tito (Imagonautas, 2018)
This paper aimed at analysing the relationship between metropolis and representation. Therefore we focus on TV series Mad Men in order to describe how, in the New York of the Sixties, consumerism and the mainstream media (Cinema, TV, Radio, Press) were the pillars on which the mass society built itself. In accordance with the same logic, in the second part, the analysis of Gossip Girl has meant to investigate and show the unchanging centrality of the metropolis in the most recent social and cultural processes driven by the digital media and the communicative modes of the social networks. The narration of the two historical periods, describes an interesting circularity between the metropolis, the historical-social phenomena that occur within it, and the medial forms of representation that describe it. These three elements establish a relation of in-turn influence in which it appears impossible to distinguish a causal succession. A metropolis like New York is thus the scenario and the protagonist of the TV representations at the same time. It is therefore possible to say that it continues to be the dominant territory and a source of inspiration for the contemporary television.